Risk assessment of gastric cancer in the presence of Helicobacter pylori cagA and hopQII genes - Guo, Xiaohui; Yin, Binghua; Wang, Can; Huo, Huazhi; Aziziaram, Zahra (Cellular and Molecular Biology, 2022)
Helicobacter pylori bacterium is one of the most common bacterial infections globally and is the leading cause of indigestion, gastric and duodenal ulcers, and gastric cancer. This bacterium can escape the antibacterial effects of stomach acid by adapting to the inner layers of the stomach. It combines with the natural sugars in the gastric mucosa. The compound is so effective that it makes bacterium resistant. For genes related to the pathogenesis of H. pylori, using the existence of genes such as cagA, hopQI, and hopQII, PCR is performed on some of these genes to amplify fragments of different lengths. One of the less-studied cases is that two or more pathogenic genes are simultaneously associated with H. pylori. This study examined the frequency of diseases and healthy individuals infected with H. pylori and cagA and hopQII genotypes. To diagnose H. pylori infection in healthy and stomach cancer patients, the PCR products are electrophoresed on the agarose gel after glmM gene amplification by PCR. To this aim, stomach tissue biopsies were used for patients, and saliva was used for healthy individuals. For this purpose, 150 gastric biopsy samples from stomach cancer patients and 150 saliva samples from healthy people were collected. Data showed a significant relationship between the coexistence of two genes, cagA and hopQII, and stomach cancer. 34.2% of patients and 10.1% of healthy individuals showed two genotypes, while other healthy people (89.9%) infected with H. pylori did not have this genotype. Therefore, the simultaneous presence of these two bacterial genes in human societies can be an essential biomarker for the diagnosis and prognosis of gastric cancer.